ANALISIS BIAYA, PENDAPATAN DAN EFISIENSI USAHATANI CABAI RAWIT (Capsicum Frutescens L) (STUDI KASUS DI KECAMATAN KEDU KABUPATEN TEMANGGUNG) - Daryatmi Daryatmi (Fakultas Pertanian UST, 2017)
The study aims to know how big the cost of the farming cayenne pepper, know the factors that affect income activity cayenne pepper and find out if the farming cayenne pepper this efficient if attenpts are made to in district Kedu. The research was carried out of December 2014 until April 2015. Basic method used in this study was descriptive analytical, methods of the implementation of the research with methods of the survey, the method of sampling of farmers wi th the method of systematic sample. The gathering data to do with a live interview as well as through registration data are already provided. Analysis of data used to see the influence of between input in used with output that was obtained in the function of the production of Cobb Douglass. Testing variables together with the F and in individuals with a t. The testing efficiency levels would be used as a t.The results showed that the area of land, the price of pepper, seeds, labor, fertilizer and pesticides in with the same effect to the production of the farming cayenne pepper. In terms of individual land area, the price, seeds, fertilizer and pesticides do not effect real, while workers have noticeable effect on the farming cayenne pepper. Testing the level of efficiency to the area of land, the price, seeds, labor, frtilizer and pesticides has not been efficient. The level income received by farmers amounting to Rp 25.336.238,8, with total cost amounting to Rp 8.181.621,66, the acquired net income of Rp 17.154.617,14 in one growing season 6 months.Keywords : Analysis, The cost, Income, Efficiency